2020
DOI: 10.3390/su13010229
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of Youth Careers in Romania—Study on the Correlation of Students’ Personal Interests with the Selected University Field of Study

Abstract: Sustainable use of resources is an act of social responsibility, in which all the factors that benefit or exploit that resource are involved. Education, with its most important goal—finding a place in the labor market in the form of a career—is a process that involves multiple financial, human and institutional resources. The present study analyzes to what extent the careers that young people in Romania build correlate with their personal interests. Using the Holland Test, the interests of a group of engineeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…In this respect, more than 40% of teachers from the European Union used telework in 2018, one of the highest prevalence within the knowledge and information and communication technologies-intensive sectors [40]. However, educational services remain open to both home-based work and face-to-face activities as work flexibility increases engagement and job satisfaction, and improves the well-being of the workers [41][42][43]. As a broad and multifaceted concept, well-being is defined as "the balance point between an individual's resource pool and the challenges faced" [44] (p. 230).…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, more than 40% of teachers from the European Union used telework in 2018, one of the highest prevalence within the knowledge and information and communication technologies-intensive sectors [40]. However, educational services remain open to both home-based work and face-to-face activities as work flexibility increases engagement and job satisfaction, and improves the well-being of the workers [41][42][43]. As a broad and multifaceted concept, well-being is defined as "the balance point between an individual's resource pool and the challenges faced" [44] (p. 230).…”
Section: Introductionmentioning
confidence: 99%
“…The attitude and behavior of young people toward tourism are important for the sustainable development of this sector (Bilan et al, 2020). Recent studies conducted in different countries show that, in general, young people have a behavior oriented toward sustainability (Cioca and Bratu, 2020), and their attitude supports the well-being of the areas visited in the long term (Šaparnienė et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This aspect is very important because many young people change their field of study along the way, which prejudices the educational system, the state that supports the educational component. There is an explicit need for support in career guidance for young people, as almost a third of students choose careers that do not coincide with their interests [45]. Over time, studies have shown that there is great efficiency in education, leading to an increase in the number of entrepreneurship programs in the education system through various forms.…”
Section: Theories Of Entrepreneurial Intentionsmentioning
confidence: 99%